The Impact Of Hyperuricemia On Cardiometabolic Risk Factors In Patients With Diabetes Mellitus: A Cross-Sectional Study - Gaita L; Timar R; Lupascu N; Roman D; Albai A; Potre O; Timar B (Diabetes, Metabolic Syndrome and Obesity, 2019)
Laura Gaita,1 Romulus Timar,1,2 Nicoleta Lupascu,1 Deiana Roman,1 Alin Albai,1,2 Ovidiu Potre,3,4 Bogdan Timar2,5 1Second Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 2Department of Diabetes and Metabolic Diseases, “Pius Brinzeu” Emergency Hospital, Timisoara, Romania; 3First Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 4Department of Hematology, Municipal Emergency Hospital, Timisoara, Romania; 5Department of Functional Sciences, “Victor Babes” University of Medicine and Pharmacy, Timisoara, RomaniaCorrespondence: Romulus TimarSecond Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy, 2 Eftimie Murgu, Timisoara 300041, RomaniaTel +4 0748 331 294Email timar.romulus@umft.roPurpose: Hyperuricemia (HUA) is linked to a variety of non-communicable diseases such as atherosclerotic cardiovascular disease (ASCVD), chronic kidney disease (CKD) and hypertension, with evidence showing its role in the development of diabetes mellitus (DM). Our study’s main aim was to explore the associations of HUA with other traditional risk factors in Romanian patients with DM and to assess the impact of the increase of serum UA on DM complications and HbA1c.Patients and methods: In this cross-sectional, non-interventional study, we enrolled, according to a population-based, consecutive-case principle, 133 patients previously diagnosed with DM. HbA1c, uric acid, lipid profile, urinary albumin/creatinine ratio, glomerular filtration rate, TSH and FT4 measurements were performed, while the diagnosis of retinopathy and of diabetic neuropathy was established using standardized methods.Results: An increased uric acid level was associated with a significant increase in the risk for development of stroke (OR=1.526; p=0.004). A weak, positive and statistically significant correlation can also be observed between the BMI and the presence of hyperuricemia (r=0.131; p=0.034), and between the triglyceride levels and hyperuricemia (r= 0.173; p=0.004). Glomerular filtration rate was correlated to hyperuricemia in a strong and negative manner, having an important statistical significance (r=−0.818; p=0.003). In our study, UA levels and HbA1c were negatively correlated, without reaching statistical significance.Conclusion: Serum UA is strongly correlated with the BMI, triglyceride level and GFR in Romanian patients with DM and HUA is significantly associated with a higher risk of stroke in these individuals.Keywords: uric acid, diabetes mellitus, metabolic syndrome, chronic diseases